Kinerja jaringan saraf berbasis backpropagation dan LVQ sebagai algoritme fingerprint RSS LoRa untuk penentuan posisi pada ruang terbuka - Misbahuddin Misbahuddin; Muhamad Syamsu Iqbal; Giri Wahyu Wiriasto; L Ahmad; S. Irfan Akbar; Muhammad Irwan (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2020)
Outdoor positioning is one of the important applications in the Internet of things (IoT). The usage of GPS is unsuitable for low-power IoT devices. Alternatively, it can use the LoRa devices. This research aims to find a better method as the fingerprint algorithm for determining the outdoor position using RSS LoRa. The methods used as the fingerprint algorithm were two artificial neural network models, i.e. backpropagation (BP) with four types of training methods and learning vector quantization (LVQ) with two types of training methods. The experiment results show the performance of LVQ1 better than those of LVQ2. Besides, the LVQ1 was also better than the BP method. However, both BP and LVQ2 have a performance that is almost similar to about 70 %. Both of the artificial neural network models, BP and LVQ, can be used as a fingerprint algorithm to determine quite accurate the outdoor object position.